1983
DOI: 10.1152/ajpcell.1983.245.1.c52
|View full text |Cite
|
Sign up to set email alerts
|

Role of particle interaction on distribution of liver lysosomes in colloidal silica

Abstract: Rat liver mitochondrial-lysosomal fractions were separated on gradients of colloidal silica. Lysosomal enzymes were distributed bimodally. The dense peak (1.117 g/ml) was nearly free from contaminants; beta-N-acetyl-D-glucosaminidase was enriched nearly 60-fold. By contrast, the buoyant peak (1.085 g/ml) co-sedimented with mitochondria, microsomes, peroxisomes, and Golgi particles. Decreasing the amount of protein layered on the gradient medium or dispersing a full sample through it shifted lysosomal marker fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The population of greater density was shown to consist of secondary lysosomes containing mature lysosomal enzymes (29)(30)(31). The population oflesser density was shown to contain elements of the Golgi apparatus and endoplasmic reticulum by Rome et al (31) and autophagic vacuoles by Surmacz et al (32). Several studies (11,(29)(30)(31)(32)(33) suggest that a bimodal distribution of lysosomal enzymes may reflect the intracellular synthesis and processing of lysosomal enzymes-i.e., precursor or latent forms of the enzymes are found in the lighter fraction and mature enzymes in the heavier.…”
Section: Discussionmentioning
confidence: 99%
“…The population of greater density was shown to consist of secondary lysosomes containing mature lysosomal enzymes (29)(30)(31). The population oflesser density was shown to contain elements of the Golgi apparatus and endoplasmic reticulum by Rome et al (31) and autophagic vacuoles by Surmacz et al (32). Several studies (11,(29)(30)(31)(32)(33) suggest that a bimodal distribution of lysosomal enzymes may reflect the intracellular synthesis and processing of lysosomal enzymes-i.e., precursor or latent forms of the enzymes are found in the lighter fraction and mature enzymes in the heavier.…”
Section: Discussionmentioning
confidence: 99%
“…A mixture of 60% Percoll and 0.75% PVP was finally chosen, in which the profile consisted of a major buoyant peak (d= 1.090) and a minor dense peak (d= 1.131), quite similar to the profile obtained previously (19). However, this /9-hexosaminidase profile obtained from isolated hepatocytes was quite different from that in liver perfusion study (10,11,20). In order to test if this was the result of a difference in gradient media or lysosomal population in these two preparations, they were directly compared under the same gradient conditions (Fig.…”
Section: Separation Of Autophagy-related Vacuoles By Percoll-pvp Densitymentioning
confidence: 93%
“…For the present study, which aims to separate subpopulations among autophagy-related vacuoles rather than to purify them from other organelles such as mitochondria, a colloidal silica was chosen. Previous studies (10,11) demonstrated that autophagic vacuoles (AV) induced in the perfused liver could be effectively separated from DB using Ludox, a colloidal silica, mixed with polyvinylpyrrolidone (PVP) , and this has been regarded as the best separation technique of AVd and DB, intermediate and late compartments of autophagy, respectively. We applied this method to freshly isolated rat hepatocytes using Percoll, a more readily available colloidal silica than Ludox.…”
mentioning
confidence: 99%
“…Colloidal-silica/PVP gradients For measurement of the distribution of lysosomes in colloidal-silica gradients, livers were homogenized after the 40 min single-pass perfusion as in Neely et al (1974). Mitochondrial and lysosomal fractions, separated from the total homogenate by differential centrifugation, were layered on colloidal silica/PVP; centrifugation and fractionation of the gradients were as in Surmacz et al (1983). Analytical Valine in perfusate plasma was analysed chromatographically (Mortimore & Mondon, 1970).…”
Section: Proteolysismentioning
confidence: 99%
“…Plasma ammonia was measured enzymically without protein precipitation, with the use of an assay kit from Boehringer (Mannheim, Germany) and a Gilford 3500 analyser. Hexosaminidase in the colloidal-silica/PVP gradient fractions and protein were determined as in Surmacz et al (1983). Electron microscopy Livers were fixed and processed for electron microscopy as in Mortimore & Schworer (1977).…”
Section: Proteolysismentioning
confidence: 99%